Semantiske sprogressourcer - mellem sprogteknologi og leksikografi - Pedersen, Bolette Sandford (LexicoNordica, 2010)
This paper discusses the synergy between lexicography and semantic language resources meant for computational use; before, now and in the future. On the basis of a brief historical overview of the backgrounds for language technology and lexicography, respectively, I analyze why the two fields have not always cooperated as closely as one would think useful. I give a recent example of a project that has exploited the similarities between the two fields by reusing a monolingual dictionary for the compilation of a Danish wordnet for technological use: DanNet. I describe some areas where modifications have been necessary in the reuse process; this regards in particular the adjustment of hyponymy hierarchies and the spellingout of underspecified information. I conclude that the two fields will most presumably be much more connected in the future due to recent corpus and editing tools which help exploit more radically the intersection between the two areas.